Dampak Putusan Arbitrase Laut China Selatan pada Pengembangan Bersama Minyak dan Gas Bumi (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2023)
After the South China Sea arbitral award stating that China had no right to claim over sea zones beyond the jurisdiction provided by the 1982 United Nations Convention on the Law of the Sea (UNCLOS 1982), China and the Philippines restarted negotiations on Joint development of oil and gas. Philippine jurists have criticized this effort as a “neglect“ or “compromise“ to the Permanent Court of Arbitration award and the Philippines' claims to the South China Sea. This article aims to analyze the implications of the Permanent Court of Arbitration award in the case of the South China Sea concerning the joint oil and gas development between China and the Philippines. This article uses doctrinal research with legal, case, and conceptual approaches. This analysis results show that after the issuance of the arbitral award, the Philippines is not obliged to negotiate provisional arrangements for the joint development of oil and gas with China following Articles 74(3) and 83(3) of the 1982 UNCLOS in the disputed area in the South China Sea. Based on the arbitral award, the Philippines is not obliged to restrain itself in areas that are not China's rights. In addition, even if the Philippines enters into joint development with China, it will not result in China being able to claim the maritime area AbstrakSetelah putusan arbitrase Laut China Selatan yang menyatakan bahwa China tidak berhak untuk mengklaim zona laut di luar kewenangan yang diatur oleh the 1982 United Nations Convention on the Law of the Sea (UNCLOS 1982), China dan Filipina memulai kembali negosiasi tentang pengembangan bersama minyak dan gas bumi. Para ahli hukum Filipina telah mengkritik upaya ini sebagai “pengabaian” atau “kompromi” terhadap putusan pengadilan arbitrase permanen dan klaim Filipina atas Laut China Selatan. Artikel ini bertujuan untuk menganalisis implikasi putusan Mahkamah Arbitrase Permanen atas kasus Laut China Selatan dikaitkan pada pengembangan bersama minyak dan gas bumi antara China dan Filipina. Artikel ini menggunakan jenis penelitian doktrinal dengan pendekatan hukum, kasus, dan konseptual. Hasil analisis ini menunjukkan bahwa setelah dikeluarkannya putusan arbitrase, Filipina tidak berkewajiban untuk merundingkan pengaturan sementara untuk pengembangan bersama minyak dan gas dengan China sesuai dengan Pasal 74(3) dan 83(3) UNCLOS 1982 di wilayah yang disengketakan di Laut Cina Selatan. Berdasarkan putusan arbitrase tersebut, Filipina tidak berkewajiban menahan diri di wilayah yang bukan merupakan hak China. Selain itu, walaupun Filipina mengadakan pengembangan bersama dengan China, itu tidak akan mengakibatkan China dapat mengklaim wilayah maritim tersebut.